Manuskrip Buton: Keistimewaan dan nilai budaya - Hiroko K. Yamaguchi, (Universiti Kebangsaan Malaysia, 2007)
The kingdom of Buton (Wolio), established in the 14th century on Buton Island and ended in 1960, left behind various kinds of historical manuscripts. Some 350 of these were owned by the late Abdul Mulku Zahari, secretary to the last sultan of Buton. A huge number of others are owned privately. This article is divided into three parts. The first part outlines the characteristics of the manuscripts in Abdul Mulku Zahari’s collection. In the second part, manuscripts written in Jawi Wolio are studied from historical and cultural points of view. In the third part, some points for further research on Buton’s manuscripts are suggested